STRATEGI PEMENANGAN TIM SUKSES PASANGAN MUHAMMAD WARDAN-SYAMSUDIN UTI DALAM MEMENANGKAN PEMILIHAN KEPALA DAERAH DI KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR TAHUN 2018 - Sagitriski, Yolla; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study entitled "The Strategy of Winning the Success Team of Muhammad Wardan-Syamsudin Uti Pair in the Election of Regional Head of Indragiri Hilir Regency in Keritang District in 2018". This study aims to determine the winning strategies of the Muhammad Wardan-Syamsudin Uti success team in the Indragiri Hilir Regional Election in Keritang District and the factors supporting the victory of Muhammad Wardan-Syamsudin Uti.            The method used in this research is qualitative method. Data collection techniques used were interviews, observation and documentation. While the data used are primary data obtained from research sites in the form of research informants, which are then supported by secondary data in the form of document data.            The results of this study indicate that the winning strategy of the Muhammad Wardan-Syamsudin Uti success team in the Indragiri Hilir District Election in Keritang District uses a defensive and offensive strategy. The offensive strategy is carried out by expanding the market and penetrating the market. This market expansion is carried out with political campaigns and political implementation while penetrating the market is done by giving new offers and approaching political figures. While the defensive strategy is carried out by maintaining permanent voters and strengthening the understanding of seasonal voters. Furthermore, the factors supporting the victory of Muhammad Wardan-Syamsudin Uti's pair in Keritang Subdistrict are the candidate participant factor, the vision and mission factor, the length of stay factor and the support factor of political figures. Keywords: Campaign Strategy, Offensive Strategy, Defensive Strategy